Entrepreneurial Law in the Field of Health Services in Electronic Medical Records - Sultan, Muh Arsul Haq; Makanung, Rudy; Ansar, Muhammad Aksa; Leleallo, Wisye Riska; Wiyanti, Ayu Sri; Alrahmi, Nurul; Wahyuningsih, Sri (Universitas Wiralodra, 2025)
Entrepreneurship in the field of Electronic Medical Records (EMR)-based healthcare services presents both opportunities and challenges related to legal compliance, patient data protection, and professional ethics. This study aims to analyze the relevant legal aspects of EMR implementation and their implications for business model development and healthcare service innovation.The method used is a systematic literature study with a qualitative-descriptive approach. Literature was obtained from academic databases and public repositories using the keywords